Pengaruh Adanya Kipas yang Mengalirkan Udara Melintasi Kondensor terhadap COP dan Efisiensi Mesin Pendingin Showcase - Wibowo Kusbandono; PK Purwadi (Retii, 2016)
The purpose of this study was to determine the effect of air flow through or across the condenser on the characteristics of refrigeration showcase. Airflow across the condenser in this study carried out by a fan mounted near the condenser. Characteristics of refrigeration showcase examined included Coefficien of Performance (COP) and efficiency. Research carried out on showcase refrigeration works by using the vapor compression cycle. The vapor compression cycle, has major components: a compressor, evaporator, capillary tube and condenser. Another component is installed filter and tool control temperature inside the cold room showcase. The compressor of the showcase that is used has a power of 1/6 PK, while the other main component size adjusts to the amount of power the compressor. R134a refrigerants used are environmentally friendly. Variations of research conducted on the number of fans that works used in the condenser air stream which passes through: (a) without fan (b) 1 fan is working and (c) 2 fan is working. Fans cool air flow that is used each have the power: 63 watts. Showcase space size: 170 cm x 55 cm x 40 cm. The cooling load in the form of 20 bottles of water by volume per 1 liter bottle of water. Research results: the flow of air passing through the condenser effect on the value of the COP and engine efficiency showcase: (1) to the condenser without a fan, the COP value of 3.23 and an efficiency of 0.76 (2) to the condenser with 1 fan, COP value of 3.56 and an efficiency of 0.77 and (3) to the condenser with 2 fans, COP value of 3.80 and an efficiency of 0.81. Keywords: showcase, vapor-compression, condenser, air-flow.